Asia-Pacific symposium on mangrove ecosystems : (Kluwer Academic, 1995)
Mangrove ecosystems are typical formations found in coastal deposits of mud and silt throughout the tropics and some distance into the subtropical latitudes. The total wordwide mangrove area, which is estimated at about 170,000 km2 with some sixty species of trees and shrubs exclusive to the habitat, dominates approximately 75% of the world's coastline between latitudes 25Â°N and 25Â°S. Such unique intertidal ecosystems support genetically diverse communities of terrestrial and aquatic organisms that are of direct or indirect socioeconomic values. Mangrove forests play important roles as coastal stabilization and protection against winds and storms; producers of nutrients, forest resources and animal species of economic importance. Recently, the issues on the conservation, proper utilization and management of mangrove forests have been widely discussed. Unfortunately, overexploitation and destruction of mangroves seriously threatens the sustainability of such a unique ecosystem. This volume includes papers on three main areas: recent advances in mangrove ecology; application and utilization of mangrove resources; and conservation and management of the ecosystems.